EFISIENSI EKONOMI USAHATANI MELON DI KECAMATAN WEDI, KABUPATEN KLATEN (ECONOMIC EFFICIENCY OF MELON FARM AT KABUPATEN KLATEN) - Yekti, Ananti (Jurnal Ilmu-Ilmu Pertanian, 2005)
The objectives of this study were to know : ( I ) the factors that affected income, and (2) the economic efficiency of melo farm. The study was conduct at Desa Pesu and Desa Jiwo Wetan, the main melo production area ok Kecamatan Wedi, Kabupaten Klaten. The method of sample selection was random with 60 respondents who planted melon on 2003. Some factors that affected the real income per hectar were real price of seed, real price of NPK fertilizer, real price of powder pesticides, real wage of hired labor and farm size. The melon farm per hectares were not economically efficient.